Serological and molecular epidemiology of foot‐and‐mouth disease viruses in agro‐pastoralist livestock herds in the kachia grazing reserve, Nigeria. Issue 4 (15th May 2019) - Ehizibolo, David Odion; De Vleeschauwer, Annebel Renate; Haegeman, Andy; Lefebvre, David; Nwosuh, Chika I.; Umoh, Jarlath U.; Okolocha, Emmanuel C.; Kazeem, Haruna M.; Van Borm, Steven; De Clercq, Kris
Summary: The Kachia Grazing Reserve (KGR) is located in Kaduna state in north‐western Nigeria and consists of 6 contiguous blocks housing 744 defined households (HH), all engaged in livestock keeping. It is considered as a homogenous epidemiological unit and a defined study area. In 2012, all cattle and sheep of 40 selected HH were sampled to determine sero‐prevalence of antibodies to foot‐and‐mouth disease virus (FMDV) and of FMDV. The overall sero‐prevalence of antibodies to the non‐structural 3ABC protein (NSP‐3ABC ELISA) was 28.9% (380/1, 315) (30.6% cattle; 16.3% sheep), and in 4.5% (62/1, 380) (5% cattle; 0.6% sheep) of the examined sera FMD viral RNA could be detected by real‐time RT‐PCR (rRT‐PCR). Additionally, in 2012 and 2014 serum, epithelium and probang samples were collected from cattle in reported FMD outbreaks and the causative FMDVs were molecularly characterized. Approximately half (28/59) of the outbreak sera reacted positive in NSP‐3ABC ELISA, and 88% (52/59) of the outbreak sera contained detectable viral RNA. Overall, antibodies against five FMDV serotypes (O, A, SAT1, SAT2 and SAT3) were detected by solid phase competitive ELISA with combinations of two or more serotypes being common. Of the 21 FMDVs that could be isolated 19 were sequenced and 18 were confirmed as SAT2 (lineage VII) while one was characterized as serotype O (EA‐3 topotype). Phylogenetic analysis revealed a close relationship between Nigerian FMDV strains and strains in this region and even with strains in North‐Africa. Our findings indicate that FMD constitutes an endemic health problem to cattle rearing in the agro‐pastoralist community in the KGR and that the KGR is not a closed epidemiological unit. Insight into the local FMDV epidemiology and in the circulating FMDV serotypes/strains is of support to the relevant authorities in Nigeria when considering the need for an FMD control policy to improve animal production in grazing reserves.